Brand Culture and Sports Consumption Behaviour: Drivers and Economic Effects - The Case of the NBA - Yang, Ziming (Transactions on Economics, Business and Management Research, 2024)
Basketball is one of the hottest sports in the world and there are a large number of basketball enthusiasts around the globe who love to play the game. Therefore, sports products related to basketball have always received a lot of attention from many basketball enthusiasts. Especially with the birth of business leagues such as the NBA, businesses have been able to advertise their products around the world more easily and increase the value of their products through endorsements from basketball superstars with large fan bases. However, most of the companies that can benefit at once are leading companies. It is difficult for small sports industries to develop their own industries by launching brand new products in the same way as they are monopolised by the leading companies. So the author will analyse how this approach can benefit more small businesses from the perspective of the drivers of consumer spending and the economic effects it brings.